2023
DOI: 10.3389/fpls.2023.1130477
|View full text |Cite
|
Sign up to set email alerts
|

C:N:P stoichiometric variations of herbs and its relationships with soil properties and species relative abundance along the Xiaokai River irrigation in the Yellow River Delta, China

Abstract: IntroductionSoil salinity is known to affect plant performance and nutrient stoichiometry by altering their ecophysiology, and thus playing a crucial role in determining plant distribution patterns and nutrient cycles in salinized ecosystems. However, there was little consensus on the effects of salinity stress on plant C, N, and P stoichiometries. Moreover, determining the relationships between species relative species abundance and plant C, N, and P stoichiometries can help to understand the different adapti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 116 publications
(172 reference statements)
0
1
0
Order By: Relevance
“…Second, plant life form that reflects the adaptive strategies of plants to environmental conditions plays an important role in shaping leaf N and P stoichiometry (Han et al., 2005; He et al., 2008; Wright et al., 2004). Third, studies have shown that leaf N and P reflect the availability of these elements in soils (Aerts & Chapin, 2000; Hobbie & Gough, 2002; Jiang et al., 2023; Suo et al., 2016), highlighting the strong impact of soil nutrients on leaf N and P stoichiometry (Vitousek & Farrington, 1997; Wen et al., 2022). For example, a case study of 126 plant species in a subtropical mountainous region of China found that soil P was the primary determiner of community leaf P and N:P ratio (Yan et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Second, plant life form that reflects the adaptive strategies of plants to environmental conditions plays an important role in shaping leaf N and P stoichiometry (Han et al., 2005; He et al., 2008; Wright et al., 2004). Third, studies have shown that leaf N and P reflect the availability of these elements in soils (Aerts & Chapin, 2000; Hobbie & Gough, 2002; Jiang et al., 2023; Suo et al., 2016), highlighting the strong impact of soil nutrients on leaf N and P stoichiometry (Vitousek & Farrington, 1997; Wen et al., 2022). For example, a case study of 126 plant species in a subtropical mountainous region of China found that soil P was the primary determiner of community leaf P and N:P ratio (Yan et al., 2015).…”
Section: Introductionmentioning
confidence: 99%